266 INFLAMMATORY PSEUDOTUMOR OF THE LIVER. (1st January 2005) - Silver, A.; Helmy, M.; Yedavalli, R. V.; Cohen, A. J.
Abstract : Background: Inflammatory pseudotumor is a rare, benign entity characterized histologically as a well-circumscribed, reactive fibroinflammatory process. The liver is a common site of involvement. While its precise etiology is unknown, it is postulated to arise as the result of an exaggerated reaction to a prior intraabdominal infectious or inflammatory process. Clinical and imaging features are non-specific, with the diagnosis often made by exclusion only after extensive laboratory and surgical evaluations. Nonetheless, this entity should be considered in the workup of hepatic masses to avoid unnecessarily aggressive intervention since most cases resolve spontaneously or with conservative management. Methods: An 18 year-old male presented to our institution with a 2-week history of right upper quadrant abdominal pain, fever, chills, and anorexia. Physical examination revealed hepatomegaly and laboratory evaluation was remarkable only for a mild leukocytosis. The patient had a history of perforated appendicitis at age 12 that was complicated by repeated bowel obstructions in the following months requiring multiple surgical interventions. Results: Initial computed tomography (CT) imaging revealed a heterogeneous, enhancing 8×6×10 cm mass in the right lobe of the liver. During hospitalization, the patient received multiple antimicrobial therapies and underwent two percutaneous CT-guided biopsies. Histological specimens revealed normal hepatocytes and all tumor marker and microbial assays were negative both at initial presentation and upon subsequent evaluations. The patient was discharged home three weeks later following cessation of all medical treatment. Repeat CT imaging demonstrated complete resolution of the mass eleven months later. Conclusion: As a rare entity with non-specific clinical and imaging features, inflammatory pseudotumor often poses a diagnostic dilemma. Consideration of this entity in the differential diagnosis and workup of liver lesions, especially in patients with a history of intraabdominal infectious or inflammatory disease, may aid in proper diagnosis and obviate the need for unnecessary surgical intervention.